СУР РАНГЛИ ҚОРАКЎЛ ТЕРИЛАРИНИНГ ТОВАРЛИК ХУСУСИЯТЛАРИ - Турганбаев, Р.У. (SCIENCE and SOCIETY, 2018)
The article is devoted to the description of such trade qualities of astrakhan sheep as hair’s length, brilliance and silkiness of hair covering of astrakhan sheep sur of Karakalpak petrean type.